Anthropometric characteristics and body composition changes in a five-time Olympic champion in Greco-Roman wrestling: A longitudinal case study towards the Paris 2024 Olympic Games - Carvajal-Veitía, W.; Herrera-Amante, C. A.; Yáñez-Sepúlveda, R.; Gainza-Pérez, V.; Deturnell-Campos, Y.; Cristi-Montero, C.; Cortés-Roco, G.; Ramos-García, C. O. (Journal of Functional Morphology and Kinesiology, 2025)
Purpose: This case study examines the anthropometric characteristics and body composition changes of a 41-year-old Cuban Greco-Roman 130 kg wrestler, a five-time Olympic gold medalist (2008-2024). To optimize his preparation for the Paris 2024 Olympic Games, another athlete participated in the qualifying process, allowing him to train without competition gear. Methods: The study monitored changes in body composition using anthropometry and bioelectrical impedance analysis (BIA) at three key time points in 2024: January, June, and July. The final assessment occurred 25 days before the Olympic event, coinciding with the final phase of his preparation. Results: The analysis revealed a significant reduction in total body mass, from 150 kg in January to 138.5 kg in July, with fat mass decreasing from 37.06 kg (24.11%) to 29.7 kg (21.5%). Muscle mass decreased slightly (77.41 kg to 72.3 kg), while bone mass remained stable. The somatotype classification was endomorphic-mesomorphic at all assessments, with slight shifts in its components (4.6-10.4-0.1 in January to 4.4-10.3-0.1 in July), reflecting an improved muscle-fat ratio. Notably, hydration levels and cellular integrity remained stable, as indicated by BIVA analysis. Conclusions: This study provides insight into the anthropometric characteristics and body composition of an elite Greco-Roman wrestler, as well as the changes observed during his preparation for his final Olympic participation. These data serve as a valuable reference for wrestlers and sports professionals, highlighting the physical profile of one of the most emblematic figures in Olympic history.